Attitude and Vaccination Status of Healthcare Workers against Hepatitis B Infection in a Teaching Hospital, Ethiopia - Mohammed Akibu; Sodere Nurgi; Mesfin Tadese; Wendwesen Dibekulu Tsega (Scientifica)
Background. World Health Organization and Centers for Disease Control and Prevention recommend all health professionals to get vaccinated against hepatitis B virus before they start the clinical attachments during their stay in the medical school. However, only 18–39% of healthcare workers in low- and middle-income countries received the vaccine. Therefore, this study aims to determine the attitude and vaccination status of health professionals working at Adama General Hospital and Medical College. Methods. An institution-based cross-sectional study was conducted from December 2016 to February 2017 with 403 health professionals working at Adama General Hospital and Medical College. Data were collected using self-administered questionnaire distributed at the participant’s work unit and analyzed using SPSS version 20. Multiple logistic regression analysis was conducted to identify factors that affect the complete vaccination status and p value < 0.05 was considered statistically significant. Result. The prevalence of complete vaccination against hepatitis B virus was 25.6%. The most frequently mentioned reasons for not being vaccinated were high cost of the vaccine (41%) and unavailability of the vaccine (36%). More than three-fourths (77.8%) of study participants strongly agreed that hepatitis B is a major public health threat and there was tendency among participants to believe that their profession will put them at increased risk of acquiring the disease (strongly agreed: 75.9%). Attending infection-prevention training [AOR = 2.3; 95% CI, 1.24–6.31], history of exposure to risky behavior [AOR = 5.5; 95% CI, 2.86–9.29], and long years of work experience [AOR = 3.1; 95% CI, 1.98–5.24] were statistically significant with complete vaccination status. Conclusion. Only one-quarter of health professionals received the recommended full dose of the vaccine. Sustained hepatitis B vaccination programs for healthcare workers need to be established by collaboration of different stakeholders to optimize health professionals’ safety against this contagious infection.